Проблемы реформирования местного самоуправления и территориальной организации власти в Украине: правовой и социально-территориальный аспекты - Емельянов, Владимир; Шульга, Анастасия (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2019)
The article discusses some legal and socio-territorial problems of reforming local government and the territorial organization of power in Ukraine, especially in the context of the formation of self-governing territorial communities. The need to make appropriate amendments to the Constitution of Ukraine regarding the planned reform, and to adopt the new Law On Local Self-Government, is emphasized. The article describes the criteria for the competencies of territorial communities while focusing on their compliance with future plans for the formation of the territories of communities. The number of united communities by region of Ukraine from 2015 to March 2018, their respective areas, and the number of inhabitants are analyzed. A general rating of the regions of Ukraine regarding the process of the formation of united communities is derived. The level of coverage by united communities of the territory of the districts of Ukraine is analyzed. The author of the article concludes that the process of forming self-governing territorial communities should be approached comprehensively and a number of measures are proposed to solve these problems.